Contrasting gene expression programs correspond with predator‐induced phenotypic plasticity within and across generations in Daphnia. Issue 19 (10th July 2017) - Hales, Nicole R.; Schield, Drew R.; Andrew, Audra L.; Card, Daren C.; Walsh, Matthew R.; Castoe, Todd A.
Abstract: Research has shown that a change in environmental conditions can alter the expression of traits during development (i.e., "within‐generation phenotypic plasticity") as well as induce heritable phenotypic responses that persist for multiple generations (i.e., "transgenerational plasticity", TGP). It has long been assumed that shifts in gene expression are tightly linked to observed trait responses at the phenotypic level. Yet, the manner in which organisms couple within‐ and TGP at the molecular level is unclear. Here we tested the influence of fish predator chemical cues on patterns of gene expression within‐ and across generations using a clone of Daphnia ambigua that is known to exhibit strong TGP but weak within‐generation plasticity. Daphnia were reared in the presence of predator cues in generation 1, and shifts in gene expression were tracked across two additional asexual experimental generations that lacked exposure to predator cues. Initial exposure to predator cues in generation 1 was linked to 50 responsive genes, but such shifts were 3–4× larger in later generations. Differentially expressed genes included those involved in reproduction, exoskeleton structure and digestion; major shifts in expression of genes encoding ribosomal proteins were also identified. Furthermore, shifts within the first‐generation and transgenerational shifts in gene expression were largely distinct in terms of the genes that were differentially expressed. Such results argue that the gene expression programmes involved in within‐ vs. transgeneration plasticity are fundamentally different. Our study provides new key insights into the plasticity of gene expression and how it relates to phenotypic plasticity in nature. Abstract : see also the Perspective by Bell and Stein